analysis of mechanical properties of ceiling boards based on corn cobs and coconut coir waste with latex adhesive - ety Jumiati; ufik eliati tumanggor; Abdul halim daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2021)
AbstractCeiling evelopment by utilizing waste corn cobs, coconut coir with gypsum flour an the adition of latex adhesive. Variations in the composition of the mixture of corn cobs, coconut coir, gypsum flour with latex adhesive include sample A (0:0:100:15), sample B (3:3:94:15), sample C (6:6:88:15), sample D (9:9:82:15), sample E (12:12:76:15), and sample F (15:15:70:15) with emphasis using a hot press and drying for 28 days. The test parameters include flexural strength and fracture strength. The test results show that sample B in the composition (3:3:94:15) is the optimal result. In this composition, the resulting ceiling board has the characteristics of a flexural strength of 3966,39 kgf/cm2 and a fracture strength of 1088,6 kgf/cm2.Keyword : Lateks , Ceiling Board, Coconut Coir, Corn Cob